Impact of Using a Constructivism Strategy to Enhance EFL University Students’ Writing Skills - Saeed Fahady, Shoaib (Opción, 2019)
This research investigates writing skills needed for EFL students and the effectiveness of mind-map strategy in improving students’ writing skills. The sample of the research consists of 80 male and female second-year students from the Department of English /College of Education for Humani- ties / University of Mosul for the Academic year 2018/2019. The sample was divided between two groups; experimental and control; 40 students each. The researcher prepared a list of EFL writing skills and posttest in writing. A set of activities was also designed by the researcher to train students by using two constructivism strategies; viz. Problem solving and mind-mapping. The results show the effectiveness of mind- mapping in developing writing skills for college level students. In the light of the findings, number of recommendations was set